TRANSFORMASI HUKUM ISLAM KE DALAM HUKUM NASIONAL INDONESIA - Ali Imron (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
There are three main sources in developing Indonesia National law, namely; custom law, law that has been established since Dutch colonial period and Islamic law. As one of the sources, Islamic law is demanded to be able to play its role in the national law. This demand is seen as a common thing as Islam as a religion has been embraced by the majority of Indonesia people. This paper is aimed at finding how to transform Islamic law into the system of Indonesia national law. The application of Islamic law in Indonesia is by transforming the bases of Islamic law and the substance of the purposes of Islamic law (maqashid syariah) into the system of Indonesia national law. This is done by chosing the bases of Islamic law which is appropriate with the characteristics of Indonesian people and with the purposes of the nation (Republic of Indonesia). There are at least three bases of Islamic law which can be transformed into Indonesia national law; i.e. the bases of fahmul mukallaf, amnesty (`afwa) and non retroactive (illa ma qad salaf). To make Indonesia national law becomes the law that is useful and put the justice for all the people, it is imperative to make an effort to dig into the values that are alive in the society and believed as honored values by the society.